Educating through the radio: an experience from the undergraduate degree in Speech Therapy (Boletín Semillero de Investigación en Familia, 2024)
Introduction: According to the World Health Organization, it is estimated that there are more than 460 million people in the world who have a disabling hearing loss. Another large number of people have a mild hearing loss and suffer from ear diseases; these can be prevented with self-care and health education so as not to cause life-threatening consequences. Objective: To describe the experience during the social projection project based on health education through radio for students of speech therapy. Materials and methods: La Corocora Saludable is the radio program of the Faculty of Health Sciences of the Universidad de los Llanos. An educational intervention of social projection was carried out during seven months, developed through the following phases: Sensitization, Consolidation of work groups. Assignment of themes for the radio programs. Preparation of scripts. Follow-up. Recording phase. Elaboration of advertising image and evaluation of the intervention.  Results: Health education was provided through the radio on topics such as the role of the speech therapist in the first level of care, strategies to work on stuttering at home, promotion and strategies for hearing care, role of the speech therapist in mental health and role in dental practice, and speech therapy management of temporomandibular joint disorders. Conclusion: Research capabilities and appropriation of topics in the training area were strengthened. Health education was provided in simple language for the community. The educational intervention was favorably evaluated.